Tribological behavior of polymer nanocomposites produced by dispersion of nanofillers in molten thermoplastics - Pesetskii, S.S.; Bogdanovich, S.P.; Myshkin, N.K.
An analysis has been made of the literature on friction and wear of polymer nanocomposites prepared by compounding nanofillers with molten thermoplastics. A process is described for preparing the nanocomposites with various binders, for example, polar and nonpolar thermoplastics, aliphatic, aromatic, and partially aromatic polymers, as well as amorphous and partially crystalline polymers by reactive extrusion. The most important group of triboengineering nanocomposites includes thermoplastics containing the following fillers, carbon nanomaterials, layered clays, metals, and metal-containing compounds. The introduction of nanofillers into thermoplastics influences the kinetics and mechanism of tribochemical transformations in a friction contact with metals or other materials. Nanofillers significantly affect the physicochemical behavior of macromolecules, as well as the macromolecular transformations, at the conditions of frictional interaction. This can be explained by adsorption (chemisorption)of functional groups found on the particle surface, variations in polymer crystallinity and morphology, constrained molecular (segmental)mobility in macrochains, and catalytic (inhibiting)effects of the additives on the course of contact reactions. As a consequence, alterations occur in the formation of transfer layers and wear debris, along with the parameters of friction. Depending on the polymer, the nature and concentration of the fillers, the latter can either improve or impair the performance parameters of friction pairs. © 2013 Elsevier B.V. All rights reserved.
Keywords: NANOFILLERS; POLYMER NANOCOMPOSITES; THERMOPLASTICS; TRIBOLOGICAL BEHAVIOR